2018
DOI: 10.1016/j.bbr.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Lateral frontal pole and relational processing: Activation patterns and connectivity profile

Abstract: The functional contribution of the lateral frontal cortex to behavior has been discussed with reference to several higher-order cognitive domains. In a separate line of research, recent studies have focused on the anatomical organization of this part of the brain. These different approaches are rarely combined. Here, we combine previous work using anatomical connectivity that identified a lateral subdivision of the human frontal pole and work that suggested a general role for rostrolateral prefrontal cortex in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 56 publications
6
35
2
Order By: Relevance
“…The fact that the unassigned striatal voxels predominantly show connectivity with these areas suggests the presence of a unique cortical-striatal loop. Based on our findings, this loop would be mostly involved in higher-order human behaviours, as are associated with FPl (Hartogsveld et al, 2018; Vendetti and Bunge, 2014), suggesting that these might be difficult to study using the translational paradigm.…”
Section: Discussionmentioning
confidence: 90%
“…The fact that the unassigned striatal voxels predominantly show connectivity with these areas suggests the presence of a unique cortical-striatal loop. Based on our findings, this loop would be mostly involved in higher-order human behaviours, as are associated with FPl (Hartogsveld et al, 2018; Vendetti and Bunge, 2014), suggesting that these might be difficult to study using the translational paradigm.…”
Section: Discussionmentioning
confidence: 90%
“…Images in the social task consisted of faces that differed on the dimensions age and ethnicity. These conditions are both described in detail in Hartogsveld et al (2017) and depicted in figure 4A. This paradigm has been shown to elicit activity in the rostrolateral prefrontal cortex (Vendetti and Bunge 2014) and a recent study (Hartogsveld et al 2017) has shown that this area is the same as the FPl identified by Neubert et al (2014).…”
Section: Methodsmentioning
confidence: 98%
“…B) This panel shows the (lack of) conjunction of the congruency effect in the AA task (red); the non-social relational reasoning (RR) effect during the task developed by Vendetti and Bunge (2014) (green); and the conjunction between the two (blue). C) This panel shows the conjunction of the congruency effect in the AA task (red); the social relational-reasoning effect during the task developed by Hartogsveld et al, (2017) (green); and the conjunction between the two (blue). For both tasks there is some overlap of effects in Area 46, but only a few voxels in FPl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations